2015
DOI: 10.1111/jre.12325
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine (interleukin‐1beta) and MMP levels in gingival crevicular fluid after use of platelet‐rich fibrin or connective tissue graft in the treatment of localized gingival recessions

Abstract: Root coverage with CAF+PRF has a significant effect on increasing gingival crevicular fluid TIMP-1 levels and suppressing gingival crevicular fluid MMP-8 and IL-β levels at 10 d. Gingival crevicular fluid levels of MMP-8, MMP-9, TIMP-1 and IL-1β did not seem to be affected by the technique at later phases of wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
1
26
0
1
Order By: Relevance
“…These molecules include metalloproteases (MMPs) and their tissue inhibitors (TIMPs), which are responsible for remodeling the tissue collagen matrix. 15,42 MMPs make up a family of proteolytic enzymes that are active in pathological and physiological processes involved in collagen remodeling and tissue repair. 40 These proteins are divided into two groups and are regulated by TIMPs, which are endogenous proteins.…”
Section: Molecular Parameters: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These molecules include metalloproteases (MMPs) and their tissue inhibitors (TIMPs), which are responsible for remodeling the tissue collagen matrix. 15,42 MMPs make up a family of proteolytic enzymes that are active in pathological and physiological processes involved in collagen remodeling and tissue repair. 40 These proteins are divided into two groups and are regulated by TIMPs, which are endogenous proteins.…”
Section: Molecular Parameters: Discussionmentioning
confidence: 99%
“…13,43 In homeostasis, MMPs and TIMPs are in equilibrium, but trauma such as that which is caused by surgery can trigger substantial metabolic and immunological reactions that disrupt this balance and affect the tissue repair process. 15,44 Despite the role of these molecules in wound healing, only one of the articles included in this review addressed the molecular aspects of the healing process. The authors evaluated changes in MMP and TIMP levels over time in the control group (SCTG) and the experimental group (PRF).…”
Section: Molecular Parameters: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leukocyte‐ and platelet‐rich fibrin (L‐PRF) has been investigated as a promising autologous source of cytokines and growth factors that favor tissue regeneration (Choukroun et al, ; Choukroun et al, ; Dohan Ehrenfest et al, ; He, Lin, Hu, Zhang, and Wu, ; Kang et al, ; Simonpieri et al, ; Ghanaati et al, ; Zhao et al, ). In clinical practice, L‐PRF has been applied in different areas that seek excellence for the healing processes of soft and hard tissues (Braccini and Dohan, ; Chang et al, ; Eren, Tervahartiala, Sorsa, and Atilla, ; Eshghpour et al, ; Canellas et al, ; Somani and Rai, ). Initially described by Choukroun, Adda, Schoeffler, and Vervelle () in France, L‐PRF is considered a second‐generation platelet concentrate and is characterized as a true autologous healing matrix (Choukroun et al, ; Dohan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that L‐PRF compressed clot alone produced favorable clinical outcomes in the treatment of infrabony periodontal defects (Chang et al, ; Zhao et al, ; Sharma and Pradeep, ; Ajwani et al, ; Chandradas et al, ), protected open wounds in the oral cavity (Asaka et al, ), sped up the healing of hard and soft tissues (Marenzi et al, ; Simon et al, ; Boora et al, ; Tunali et al, ; Eren et al, ; Kotsakis et al, ), reduced the rates of alveolitis after tooth extractions (Eshghpour et al, ; Kumar et al, ), and improved BV in preprosthetic surgeries and the osseointegration of dental implants (Oncu and Erbeyoglu, ; Castro et al, ; Cortese et al, ; Kanayama et al, ; Aoki et al, ; Oncu and Alaaddinoglu, ; Oncu et al, ; Boora et al, ; Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%